2015
DOI: 10.1158/1535-7163.mct-14-0158
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compound, NK150460, Exhibits Selective Antitumor Activity against Breast Cancer Cell Lines through Activation of Aryl Hydrocarbon Receptor

Abstract: Antiestrogen agents are commonly used to treat patients with estrogen receptor (ER)-positive breast cancer. Tamoxifen has been the mainstay of endocrine treatment for patients with early and advanced breast cancer for many years. Following tamoxifen treatment failure, however, there are still limited options for subsequent hormonal therapy. We discovered a novel compound, NK150460, that inhibits 17β-estradiol (E2)-dependent transcription without affecting binding of E2 to ER. Against our expectations, NK150460… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Similar results were observed for head and neck cancer where AhR antagonists were effective as anticancer agents [49]. The growth and invasion of breast and other cancers are inhibited by AhR agonists, and there has been development of relatively non-toxic SAhRMs which include aminoflavone and NKI150460, a novel selective anticancer agent and AhR agonist, for treatment of breast cancer [14,50]. Among the more classical AhR ligands, indole-3-carbinol (from cruciferous vegetables) and β-naphthoflavone and its dimer, diindolylmethane (DIM), exhibit promising anticancer activity and these compounds and synthetic analogs should be further investigated for their potential clinical applications.…”
Section: Role Of the Ahr In Carcinogenesismentioning
confidence: 55%
“…Similar results were observed for head and neck cancer where AhR antagonists were effective as anticancer agents [49]. The growth and invasion of breast and other cancers are inhibited by AhR agonists, and there has been development of relatively non-toxic SAhRMs which include aminoflavone and NKI150460, a novel selective anticancer agent and AhR agonist, for treatment of breast cancer [14,50]. Among the more classical AhR ligands, indole-3-carbinol (from cruciferous vegetables) and β-naphthoflavone and its dimer, diindolylmethane (DIM), exhibit promising anticancer activity and these compounds and synthetic analogs should be further investigated for their potential clinical applications.…”
Section: Role Of the Ahr In Carcinogenesismentioning
confidence: 55%
“…Added to the fact that the structure of curcumin represents myriad avenues for structural modification and pharmacological manipulation, enhancing its AHR targeting may one day produce novel chemopreventives and anticancer agents for colorectal cancer (21, 54). In fact, small molecule agonists of the AHR are already under investigation to combat cancer in other tissues (55). …”
Section: Discussionmentioning
confidence: 99%
“…Recent paradigm of promising anti-breast cancer candidates has revealed that Ahr mediates their therapeutic potential. For example, (5S,7S)-7-methyl-3-(3-(trifluoromethyl)phenyl)-5,6,7,8-tetrahydrocinnolin-5-ol (NK150460) suppresses growth of different estrogen receptor (ER)-negative and ER-positive breast cancer cell lines via the molecular cascade of Ahr/Arnt [11]. The Ahr mediates the inhibitory effects of 2-(4-hydroxy-3-methoxyphenyl)-benzothiazole (YL-109) on growth and invasion of MDA-MB-231 through upregulation of Hsp70-interacting protein (CHIP) [12].…”
Section: Introductionmentioning
confidence: 99%